2023
DOI: 10.21037/tp-23-185
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with feeding behaviors among mothers of obese infants: a cross-sectional study

Abstract: Background Infant obesity is a risk factor for diseases in childhood and even in adulthood. Maternal feeding behaviors are strongly associated with infant obesity, hence factors relevant to mother’s perception, socioeconomic status, and social support that influence the feeding behaviors need to be explored. Therefore, this study aimed to examine associated factors of feeding behaviors among mothers with obese infants. Methods This cross-sectional study was conducted at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…(Astutik, 2015) The research results showed that 26.9% of mothers did not control how much their baby breastfed, and 28% did not pay attention to whether the baby was showing signs of being full, and even expected the baby to drink a fixed amount during each breastfeeding session. (Hu et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…(Astutik, 2015) The research results showed that 26.9% of mothers did not control how much their baby breastfed, and 28% did not pay attention to whether the baby was showing signs of being full, and even expected the baby to drink a fixed amount during each breastfeeding session. (Hu et al, 2023).…”
Section: Discussionmentioning
confidence: 99%